HUBUNGAN PEMAHAMAN TENTANG MAKANAN BERPROTEIN DENGAN POLA LATIHAN PARA BINARAGA - Shandy, Roby Sandra Ary; Suranto, Suranto; Tarigan, Herman (JUPE, 2014)
The objective of this study was to determine whether there is a relationship of understanding of the pattern of protein foods with bodybuilding exercises on the fitness center of Bandar Lampung hercules. The research methodology used is descriptive analytical method, with a sample of 40 respondents fitness center of Bandar Lampung. Data collected through questionnaires understanding of protein foods. Exercise patterns obtained by observation. The results showed no significant relationship between the understanding of protein foods with exercise pattern (p = 0.011). Average pattern of practice in bodybuilding is correct. The number of respondents as many as 40 people. A total of 21 respondents have a good exercise regimen (52.5%) and a total of 19 respondents have less training pattern (47.5%). The majority of respondents have a good understanding of as many as 25 (62.5%) and has a lack of understanding as much as 15 (37.5%).ÃÂ Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui apakah ada hubungan pemahaman tentang makanan berprotein dengan pola latihan pada para Binaraga dipusat kebugaran hercules Bandar Lampung. Metodologi penekitian yang digunakan adalah metode deskriptif analitik, dengan sampel sebesar 40 responden dipusat kebugaran Bandar Lampung. Data dikumpulkan melalui angket pemahaman tentang makanan berprotein. Pola latihandiperoleh dengan cara observasi. Hasil penelitian menunjukkan ada hubungan signifikan antara pemahaman tentang makanan berprotein dengan pola latihan (p=0,011). Rata-rata pola latihan pada binaraga sudah benar. Jumlah responden sebanyak 40 orang. Sebanyak 21 responden memiliki pola latihan baik (52,5%) dan sebanyak 19 responden memiliki pola latihan kurang (47,5 %). Sebagian besar reponden memiliki pemahaman baik sebanyak 25 (62,5%) dan memiliki yang pemahaman kurang sebanyak 15 (37,5%).Kata kunci : binaraga, pemahaman makanan berprotein, pola latihan.